IMPLEMENTASI METODE AN NASHR DALAM MENGHAFAL JUZ 30 DI MADRASAH TSANAWIYAH BABUL FUTUH PANDAAN - Faizatul Maslukhah; Maskuri Maskuri; Muhammad Sulistiono (VICRATINA, 2021)
In Islamic religious education, the main basis or main source of Islamic teachings is the holy book of the Qur'an. One way to preserve the Qur'an is to teach it and instill the ability to read and memorize from an early age. Of course, starting from memorizing and understanding the short letters contained in chapter amma or chapter 30. In order for the teaching and learning process to be carried out as desired, a method is needed. The method is a set of methods and techniques used by educators in the learning process, for example the An Nasr method. The An Nasr method helps students memorize Juz 30. This study uses a qualitative approach, the type of case study research with data collection techniques, namely observation, interviews, and documentation. The research findings at Madrasah Tsanawiyah Babul Futuh Pandaan are: 1) there are seven formulation and design processes in learning the An Nasr method, including: identification, selection, modification, organizing, communication and socialization, teaching, and evaluation. 2) the process of implementing the An Nasr method in memorizing Juz 30 is carried out in the classroom and outside the classroom. 3) students' memorization results include: students are able to translate the Koran (Words), are able to memorize the Koran well, are able to distinguish the meaning of the same word but used in different contexts, students know more vocabulary in Arabic (mufrodat), and increase students' motivation in memorizing.